Prevalence and antimicrobial susceptibility of Vibrio parahaemolyticus isolated from retail shrimps in Malaysia - Letchumanan, Vengadesh; Yin, Wai-Fong; Lee, Learn-Han; Chan, Kok-Gan (Frontiers in Microbiology, 2015)
Vibrio parahaemolyticus is a marine and estuarine bacterium that has been the leading cause of foodborne outbreaks which leads to a significant threat to human health worldwide. Consumption of seafood contaminated with Vibrio parahaemolyticus causes acute gastroenteritis in individuals. The bacterium poses two main virulence factor including the thermostable direct hemolysin (tdh) which is a pore-forming protein that contributes to the invasiveness of the bacterium in humans and TDH-related hemolysin (trh), which plays a similar role as thermostable direct hemolysin (tdh) in the disease pathogenesis. This study aimed to investigate the antimicrobial resistance Vibrio parahaemolyticus strains in shrimps purchased from wetmarkets and supermarkets. The toxR-based PCR assay indicated that a total of 57.8% (185/320) isolates were positive for V. parahaemolyticus. Only 10% (19/185) toxR-positive isolate exhibit the TDH-related hemolysin (trh) gene and none of the isolates were tested positive for thermostable direct hemolysin (tdh). The MAR index was measured for 14 common antimicrobial agents. The results indicated 98% of the isolates were highly susceptible to imipenem, ampicillin sulbactam (96%), chloramphenicol (95%), trimethoprim-sulfamet (93%), gentamicin (85%), levofloxacin (83%) and tetracycline (82%). The chloramphenicol (catA2) and kanamycin (aphA-3) resistance genes were detected in the resistant V. parahaemolyticus isolates. Our results demonstrate that shrimps are contaminated with V. parahaemolyticus, some of which carry the trh-gene thus being potential to cause food borne illness. The occurrence of multidrug resistance strains in the environment could be an indication of excessive usage of antibiotics in agriculture and aquaculture fields.